JaSTA-2: Second version of the Java Superposition T-matrix Application - Halder, Prithish; Das, Himadri Sekhar (Computer physics communications, 2017)
In this article, we announce the development of a new version of the Java Superposition T-matrix App (JaSTA-2), to study the light scattering properties of porous aggregate particles. It has been developed using Netbeans 7.1.2, which is a java integrated development environment (IDE). The JaSTA uses double precision superposition T-matrix codes for multi-sphere clusters in random orientation, developed by Mackowski and Mischenko (1996). The new version consists of two options as part of the input parameters: (i) single wavelength and (ii) multiple wavelengths. The first option (which retains the applicability of older version of JaSTA) calculates the light scattering properties of aggregates of spheres for a single wavelength at a given instant of time whereas the second option can execute the code for a multiple numbers of wavelengths in a single run. JaSTA-2 provides convenient and quicker data analysis which can be used in diverse fields like Planetary Science, Atmospheric Physics, Nanoscience, etc. This version of the software is developed for Linux platform only, and it can be operated over all the cores of a processor using the multi-threading option. Program Title: Java superposition T-matrix Application: version - 2.0 Program Files doi:http://dx.doi.org/10.17632/bbtjj8kd74.1 Licensing provisions: GPLv3 Programming language: Fortran, Java. External routines/libraries: jfreechart-1.0.14 [1] (free plotting library for java), j3d-jre-1.5.2 [2] StdDraw3D (3D visualization) Subprograms used: spline.f90, splinek.f90, wavesort.f90 Journal reference of previous version: Comput. Phys. Commun., 2014, 185, 2369 Does the new version supersede the previous version?: No. Nature of problem: Light scattering properties of cosmic dust aggregates Solution method: Java application based on Mackowski and Mishchenko’s Superposition T-Matrix code (1996). Reasons for the new version: The earlier version was mainly developed to calculate the optical properties of cosmic dust aggregates for a single wavelength in vacuum. The user had to calculate multiple times for different wavelengths to analyze the variation of different scattering parameters (e.g., phase function, polarization, the extinction efficiency, the absorption efficiency, the scattering efficiency, etc.) of aggregate particles for a range of wavelengths which was quite time-consuming. Therefore we have developed the new version of JaSTA with an ability to calculate the scattering parameters for a wide range of wavelength. In this new version, we have introduced the multi-threading option to distribute the multi-wavelength calculations to the maximum number of processing cores present in a computer. Hence the calculation time decreases considerably. Summary of revisions: Java superposition T-matrix App (JaSTA) [3] is a Java swing application developed to study the light scattering properties of cosmic dust aggregates based on the Mackowski & Mischenko’s Superposition T-matrix (STM) code [4]. This application calculates the polarization and other scattering matrix elements along with extinction, absorption, and scattering efficiencies for a single wavelength. JaSTA was solely devoted to the light scattering properties of cosmic dust aggregates. Cosmic dust includes comet dust, interplanetary dust, and interstellar dust. Many investigators studied the light scattering properties of comet dust [5]–[10], interplanetary dust [11], interstellar dust [12] using the superposition T-matrix code. JaSTA provided a much better platform for the STM code as a packaged software which can calculate light scattering properties of cosmic dust aggregates for a single wavelength in the vacuum with a click of a button and saves the results in a database so that the saved data can be re-utilized. Recently JaSTA has been used to compute the orientation-averaged scattering matrix elements for fractal aggregates of black carbon aerosols [13]. The interesting feature of the new version of JaSTA is that it can calculate the extinction efficiency at different wavelengths for a given size in a single run which is applicable in the study of interstellar extinction by aggregates at different wavelengths. To analyze the wavelength dependence of extinction one had to execute the calculation for several wavelengths by changing the wavelength and refractive indices in the input for each run in older version of JaSTA. This was very much time consuming and cumbersome. Hence this major drawback led us to rethink and re-establish JaSTA with the multi-wavelength option. JaSTA-2 is the second version of JaSTA aimed to provide the multi-wavelength facility along with the default single wavelength option. JaSTA-2 comes with some other two major updates: cubic spline interpolation of refractive index with wavelengths and multi-threading option for faster calculation. It is developed using Netbeans IDE and is available only for Linux OS. It uses jFreechart-1.0.14 java library to plot various graphs. The multi-wavelength feature will help us to extract the dependence of extinction efficiency on wavelength. Further information on the new features and applicability of JaSTA-2 are provided in the documentation file ‘ JaSTA-2_doc.pdf’, and ‘ readme.txt’ file which are available in the software package. [1]http://www.jfree.org/index.html[2]https://java3d.java.net/[3]P. Halder, A. Chakraborty, P. Deb Roy & H.S. Das, Computer Physics Communications, 185 (2014) 2369-2379.[4]D.W. Mackowski & M.I. Mischenko, J. Opt. Soc. Am. Am., 13 (1996) 2266-2278.[5]H. Kimura, L. Kolokolova & I. Mann, A&A, 407 (2003) L5-L8.[6]H. Kimura, L. Kolokolova & I. Mann, A&A, 449 (2006) 1243-1254.[7]H.S. Das, S.R. Das, T. Paul, A. Suklabaidya & A.K. Sen, MNRAS, 389 (2008) 787-791.[8]H.S. Das, S.R. Das & A.K Sen, MNRAS, 390 (2008) 1195-1199.[9]H.S. Das, A. Suklabaidya, S. Datta Majumder & A.K. Sen, Research in A&A, 10 (2010) 355-362[10]H.S. Das, D. Paul, A. Suklabaidya & A.K. Sen, MNRAS, 416 (2011) 94-100.[11]J. Lasue, A.C. Levasseur-Regourd, N. Fray & H. Cottin, A&A, 473 (2007) 641-649.[12]M. A. Iati, A. Giusto, R. Saija, F. Borghese, P. Denti, C. Cecchi-Pestellini & S. Aielo, ApJ, 615 (2004), 286.[13]A. Pandey & R. K. Chakrabarty, Optics Letters, 41 (2016) 3351-3354.